Modeling three dimensional gas bubble dynamics between two curved rigid plates using boundary integral method. (December 2019) - Aziz, Imad A.; Manmi, Kawa M.A.; Saeed, Rostam K.; Dadvand, Abdolrahman
Abstract: High speed liquid jet forms when a bubble collapses near a solid boundary. The formation of the jet has both advantages and disadvantages as it causes erosion and damage in the nearby turbomachinery and can be beneficially applied in surface cleaning, fluid pumping, etc. In this paper, three-dimensional bubble oscillation between two curved rigid plates is modeled using boundary integral method (BIM). The bubble is incepted at different locations between the plates to investigate the eccentricity effects on the bubble shape, jet formation, etc. The modified Laplacian smoothing technique is implemented on the bubble surface during the jet development to reduce element distortion. The new model is validated with the Rayleigh–Plesset equation as well as with the available experimental data. It was found that the jet velocity increases, and the number of jets is reduced from two to one as the bubble is horizontally shifted away from the centroid. When the bubble is incepted on the horizontal axisymmetric line the jet is horizontal. However, the jet direction changes as the bubble is incepted closer to one of the plates. Finally, the pressure and velocity fields of the fluid surrounding the bubble are provided for better interpretation of the results.